3D Bioprinting at the Frontier of Regenerative Medicine, Pharmaceutical, and Food Industries - Ramadan, Qasem; Zourob, Mohammed (Frontiers in Medical Technology, 2021)
3D printing technology has emerged as a key driver behind an ongoing paradigm shift in the production process of various industrial domains. The integration of 3D printing into tissue engineering, by utilizing life cells which are encapsulated in specific natural or synthetic biomaterials (e.g., hydrogels) as bioinks, is paving the way toward devising many innovating solutions for key biomedical and healthcare challenges and heralds' new frontiers in medicine, pharmaceutical, and food industries. Here, we present a synthesis of the available 3D bioprinting technology from what is found and what has been achieved in various applications and discussed the capabilities and limitations encountered in this technology.